GE_GERICHTE C/7101/2012 vom 21. August 2012 - GE Cour de justice (2012)
; BAIL À LOYER ; CONDITION DE RECEVABILITÉ ; ÉVACUATION(EN GÉNÉRAL) ; DÉFAUT DE PAIEMENT | CPC.311 CPC.318 CPC.148 CPC.257 CO.257d